STUDI KOMPARASI PRESTASI BELAJAR KELAS BINAAN ASTRA DENGAN KELAS T-TEP NON OJT PADA KOMPETENSI PERAWATAN DAN PERBAIKAN SISTEM MOTOR STARTER - Mohammad Ali Nurdin, - (2008)
The research studied main subject : "Is there any differences of the ability between the trainees of Astra class councelling and T-TEP non OJT class Majoring in Automotive Mechanical Engineering Skill at SMKN 6 Bandung in the implementation of treatment and reparation motor starter system. The subject is taken into the research because the writer saw learning capability students of astra class councelling more higher than regular one. With the new curriculum applied at SMKN 6 Bandung Majoring in Automotive Mechanical Engineering witch is T-TEP (Toyota-Technical Education Programme) curriculum, where students of Astra class councelling even students of T-TEP non OJT used the same curriculum, and standard equipment for practices also same witch is standard Toyota. With regard to above problem, The research generally has objective to obtain an accurate description concerning the comparison of learning capability between students of astra class with students of T-TEP non OJT. As basic point of the research, the writer formulated hypotheses as follow : "There is no difference of learning capability between students of astra class councelling with students of T-TEP non OJT Majoring in Automotive Mechanical Engineering at SMKN 6 Bandung." Methodologies of the research used are quasi experiment with subject based on two class, witch is 2TMO2/Astra counseling class (control class) and 2TMO5/ T-TEP non OJT class (experiment class). Quantitative approach method as main data to test hypothesis. Data which obtained with pre test data, post test and N-gain with t test for get the different value of both class. Research done to sixty nine respondences. Pursuant to result of research of treatment practice and repair of motor starter system and test t got value equal to tcount = 0,633. price of tcount compared to price of ttable level of signification 95% and dk = 68, got Pv = its 0,1668 Result tcount > ttable, hence can be concluded this un acceptable research hypothesis at level of signification 95%, with degree of freedom (dk) = 69, its meaning not there are difference of learning capability of treatment and reparation motor starter system between students of Astra's councelling class and T-TEP non OJT class at SMKN 6 Bandung.